Effects of I(Kur) blocker MK-0448 on human right atrial action potentials from patients in sinus rhythm and in permanent atrial fibrillation - Loose, Simone (Frontiers Media S.A., 2014)
Selective blockers of the Kv1.5 channel have been developed for the treatment of atrial fibrillation (AF), but little is known how these atrial-selective drugs affect human action potentials (APs). Therefore we have investigated the Kv1.5 blocker MK-0448 (N-{6-[(1S)-1-(4-fluorophenyl)-2,2-di(pyridin-3-yl)ethyl]pyridin-2-yl}methanesulfon- amide) in right atrial trabeculae from patients in sinus rhythm (SR), permanent AF (>6 months), and intermittent AF. MK-0448 blocked Kv1.5 current in an expression system and concentration-dependently elevated the plateau phase of atrial APs. In SR preparations stimulated at 1 Hz, MK-0448 (3 μM) shortened action potential duration at 90% of repolarization (APD(90)) and effective refractory period (ERP), but in permanent AF preparations, MK-0448 prolonged APD(90) and ERP. The effects of MK-0448 in intermittent AF resembled those in SR preparations. Block of I(Ks) is probably more prominent in AF because of reduced repolarization reserve due to AF-induced remodeling.